Manifestación de violencia machista en estudiantes universitarios con parejas en San Luis Potosí (Ciudad), México y Bogotá, Colombia (2021)
This research is carried out to determine the manifestations of sexist violence in university students with partners in San Luis Potosí (City) - Mexico and Bogotá - Colombia. The theoretical focus of the study is gender, since it studies the forms of masculinity and femininity that allow us to know the diversity, the nuances of gender expressions and identify the impact they have on the lives of both men and women.